EVALUASI ARAH KOMPETENSI LULUSAN PROGRAM STUDI PENDIDIKAN PROFESI APOTEKER PADA PENDIDIKAN TINGGI FARMASI DI KALIMANTAN SELATAN, INDONESIA - Muhammad Reza Pahlevi; Noval; Febrianti, Dwi Rizki; Difa Intannia; Syahrizal Ramadhani; Melviani; Mustika Muthaharah (Jurnal Insan Farmasi Indonesia, 2025)
South Kalimantan has four Pharmacy Higher Education Institutions (PTF) offering Pharmacist Professional Education Study Program (PSPPA), namely Lambung Mangkurat University (ULM), Borneo Lestari University (UNBL), Sari Mulia University (UNISM), and Muhammadiyah University of Banjarmasin (UMB). This research aims determine competency direction PSPPA graduates from PTF in South Kalimantan. Using descriptive research design qualitative case study method, the findings reveal that graduate profile PSPPA South Kalimantan does not fully reflect local and national characteristics  pharmacist, such as being religious, having national perspective, adhering professional ethics, and upholding the law. The graduate profile should encompass  institution's vision, academic excellence, moral values, specific characteristics higher education institution. PSPPA designed with min.36 credits over 2 semesters. ULM directs PSPPA competencies towards pharmaceutical practices in wetland environments, integrated into several courses. UNBL focus producing professional pharmacist with foundation Kalimantan's local wisdom, featuring integrated course pharmaceutical services. UNISM emphasizes excellence and collaboration  developing riverine potential, integrated Phytotherapy course, given South Kalimantan's, particularly Banjarmasin's, numerous river systems. Meanwhile, UMB develops PSPPA program characterized progressive Islamic value, with standout course Islamic Professionalism. The results align with graduate competency standards and pharmacist education curriculum standards  APTFI, Law No.17 of 2023, and Minister Education and Culture Regulation no.53 of 2023